Support on the remote interaction for augmented reality system - Affonso, Elaine Parra; Sementille, Antonio Carlos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This article presents a support on the remote interaction for utilization in augmented reality systems based on ARToolkit. It utilizes the multicast communication in order to improve the scalability of distributed environment. This support may be utilized in production of specific applications pointed to distance education, training and entertainment. The validity of support happened with the implementation of a prototype and realization of tests for communication latency analysis and frames per second rate. © 2007 IEEE.
Keywords: Augmented reality; Communication and interaction; Distance education; Flow interactions; Augmented reality systems; Communication latency; Distributed environments; Frames per second; International conferences; Multicast communications; Remote interaction; Virtual reality